2006
DOI: 10.1088/0953-8984/18/38/s26
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic particle hyperthermia: nanoparticle magnetism and materials development for cancer therapy

Abstract: Loss processes in magnetic nanoparticles are discussed with respect to optimization of the specific loss power (SLP) for application in tumour hyperthermia. Several types of magnetic iron oxide nanoparticles representative for different preparation methods (wet chemical precipitation, grinding, bacterial synthesis, magnetic size fractionation) are the subject of a comparative study of structural and magnetic properties. Since the specific loss power useful for hyperthermia is restricted by serious limitations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
757
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 889 publications
(782 citation statements)
references
References 48 publications
(59 reference statements)
19
757
0
6
Order By: Relevance
“…Assuming a net magnetic moment of 4 μB per formula unit (Fe3O4) as is typically calculated for magnetite and taking the density of magnetite to be 5.175 g/cm 3 , this magnetic moment density turns out to be 5.4·10 28 μB/m 3 . 25 Integration over the particle's volume yields the total magnetic field ⃗⃗ = ⃗ ⃗⃗ 0 4 3 (− sin cos , − cos sin , −2 cos ),…”
mentioning
confidence: 99%
“…Assuming a net magnetic moment of 4 μB per formula unit (Fe3O4) as is typically calculated for magnetite and taking the density of magnetite to be 5.175 g/cm 3 , this magnetic moment density turns out to be 5.4·10 28 μB/m 3 . 25 Integration over the particle's volume yields the total magnetic field ⃗⃗ = ⃗ ⃗⃗ 0 4 3 (− sin cos , − cos sin , −2 cos ),…”
mentioning
confidence: 99%
“…It appears that increasing concentration reduces the magnetic hysteresis due to dipolar coupling effects, as has also been suggested in previous works reporting similar SAR versus magnetic field evolution. 11,23 However, the cause of such decrease remains still unclear, being also conjectured to originate from a broad size distribution. Thus, with the purpose of studying the role of magnetic dipolar interactions on the hyperthermia proper- ties of the NP system, we performed MC simulations to treat the influence of particle concentration and field dependence on the SAR.…”
Section: Resultsmentioning
confidence: 99%
“…In part due to their large volume, the magnetosomes synthesized by magnetotactic bacteria produce a larger amount of heat than the chemically synthesized nanoparticles when they are exposed to an oscillating magnetic field. This has been shown for bacterial magnetosomes mixed in solution, which were either contained within the magnetotactic bacteria or extracted from these bacteria and for magnetosomes arranged in chains or forming individual nanoparticles, (6,12). In addition of producing a large amount of heat, it has been reported that the magnetosomes are not particularly toxic when they are injected in rats, (11).…”
Section: Introductionmentioning
confidence: 90%
“…The chemically synthesized nanoparticles (SPION@Citrate) were prepared following a protocol described previously, (14). To prepare non-coated γFe2O3 particles, a solution of base (dimethylamine) was first added to an aqueous micellar solution of ferrous dodecyl sulfate (Fe(DS)2) and mixed.…”
Section: Preparation Of the Different Types Of Nanoparticles Used Asmentioning
confidence: 99%